THE ROLE OF THE RUSSIAN LANGUAGE IN THE FORMATION OF SCHOOLCHILDREN’S LANGUAGE, CULTURAL AND COMMUNICATION COMPETENCES - Gaukhar Ataniyazovna Hamidullaeva (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the increase in students’ level of formation of communicative skills, the level of creativity, the level of knowledge on the subject, the level of development of thinking, the development of their own style of speech and a change in attitude to the language as a whole.